Analys av tillämpningsområdet för skattesystemets inre sammanhang som rättfärdigandegrund för skatteregler i strid med EUF-fördraget - Kjellander,Hannah (2014)
This thesis focuses on the impact of EU law on national direct taxation. National income tax rules may not restrict the free movement of the Treaty on the Functioning of the European Union (TFEU). This means that EU law has a considerable impact on national legislation in this area, even if the member states for the most part have retained their competence to legislate. A member state may, therefore, not construct an income tax rule that leads to the negative treatment of a cross-border fiscal situation in comparison to a corresponding domestic situation. Even if a national income tax rule restricts the right to free movement it may in some cases be justified by, for example, the grounds of justification developed in case law of the European Court of Justice (ECJ) with the support of the rule of reason-doctrine. A ground for justification may only be accepted by the ECJ if the restriction is appropriate to achieve the objective and proportionate in the means to attain the objective. One of these grounds of justification that have been accepted by the ECJ is the preservation of fiscal cohesion. In this thesis, the scope of application of the preservation of fiscal cohesion is analysed. The ground of justification was first applied in the case Bachmann in 1992. After this initial application, the ECJ rejected application in all following cases up until the acceptance in the case Krankenheim in 2008. The analysis focuses on the ECJ’s case law during the time after the ground of justification once again was accepted. To fulfill the purpose of the thesis, an analysis has been made of the conditions that the ECJ requires to accept the application of the ground of justification. The ECJ has required that a direct link has to be established between the tax advantage concerned and the offsetting of that advantage by a tax levy. In some previous case law, the ECJ has held that in order for the legislation to be accepted it must relate to one and the same taxpayer and the same tax. Furthermore, the principal of the fiscal cohesion may not be invoked if the fiscal cohesion has been secured on a reciprocal level by a tax treaty. Another topic of analysis is the relationship between the present ground of justification and closely related grounds of justification. The thesis ends with conclusions on the required conditions for the application of the ground of justification and whether the conditions have changed in later case law. The conclusion here is that the ECJ has upheld the requirement for the condition of a direct link also in later case law, whereas the requirement for the conditions of one and the same taxpayer and the same tax is not mentioned in all later case law. It is, therefore, unclear if the ECJ still views the two lastly mentioned conditions as a strict requirement for the acceptance of the application of the ground of justification. The conclusion is that it should be easier and more likely to achieve an acceptance of a restrictive national legislation if the two conditions are indeed met. Furthermore, I conclude that the existence of a tax treaty still affects the applicability of the ground of justification in later case law. In regards to closely related grounds of justification, I conclude that the balanced allocation of the power to impose taxes shows great similarities to the preservation of fiscal cohesion.
Keywords: skatterätt; EU-rätt; skattesystemets inre sammanhang